2001
DOI: 10.1530/eje.0.1440645
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A and leptin change inversely in fasting non-obese subjects

Abstract: Objective: Leptin, neuropeptide-Y (NPY) and orexin are peptides regulating energy metabolism and appetite control. NPY and orexin are mainly found in the central nervous system and they have also recently been found in the peripheral nervous system. We investigated how fasting affects changes in circulating concentrations of these peptides and their association with nutritional and metabolic parameters in humans. Design and methods: Ten non-obese female patients with psychosomatic disorders fasted for 7 or 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 30 publications
(38 reference statements)
5
39
3
Order By: Relevance
“…Thus, orexin cells are somehow sensing the animal's nutritional state, and OXA is released in response to nutritional depletion. In support of this idea, we found a significant increase in plasma OXA level in fasted lean rats similar to that reported in humans (14,15). The origin of plasma OXA was not identified; however, in light of the present findings, one potential source is the pancreatic islets.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, orexin cells are somehow sensing the animal's nutritional state, and OXA is released in response to nutritional depletion. In support of this idea, we found a significant increase in plasma OXA level in fasted lean rats similar to that reported in humans (14,15). The origin of plasma OXA was not identified; however, in light of the present findings, one potential source is the pancreatic islets.…”
Section: Discussionsupporting
confidence: 91%
“…Endocrine cells in the gastric and intestinal mucosa (12,13), as well as in the pancreas (12), also contain orexins; therefore, orexins may function as circulating hormones and/or paracrine or autocrine transmitters. The presence of OXA in human plasma supports this idea (14,15).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Also recently, a bidirectional association between plasma concentration of leptin and orexin as regards nicotine craving was demonstrated (von der Goltz et al, 2010). Such inverse correlation between leptin and orexin plasma levels was also found both in obese and non-obese participants (Komaki et al, 2001 andBronsky et al 2007). However, in AN-R patients studied by us, such an association was observed only initially and has not hold during the course of treatment .…”
Section: Correlation Between Leptin (Lep) and Orexin A (Oxa) Plasma Lmentioning
confidence: 89%
“…A number of observations point to an increase in the orexin A level during fasting and weight loss, and a decrease during weight gain. Komaki et al (2001) reported an increase in orexin A plasma levels in adult fasting, non-obese participants during 10 days of fasting which was followed by a reduction in orexin A plasma levels during subsequent refeeding. Bronsky et al (2007) observed a significant increase in orexin A plasma levels after a decrease of BMI from about 28 kg/m 2 to 26 kg/m 2 in fasting obese children.…”
Section: Orexin a (Oxa) Plasma Level In Patients Suffering From Anorementioning
confidence: 95%